Self Regulated Learning Calon Guru Sekolah Dasar Dalam Menyelesaikan Masalah Numerasi: Studi Deskriptif - Dian Kusmaharti; Via Yustitia (UNION : Jurnal Ilmiah Pendidikan Matematika, 2022)
This study aims to determine the level of self-regulated learning ability of elementary school teacher This study aims to determine the level of self-regulated learning ability of elementary school teacher candidates in solving numeracy problems. This research is quantitative descriptive. The research subjects were 44 prospective elementary school teacher students obtained by cluster random sampling technique. Data collection using a questionnaire. The instrument is a valid and reliable self-regulated learning questionnaire. The data analysis technique used is descriptive statistics. The results showed that the level of self-regulated learning ability of elementary school teacher candidates was in a fairly good category. The results of the analysis on each aspect are, 1) the planning aspect is in the good enough category, the activities include determining learning strategies, feeling obliged to complete the task, and organizing themselves to prepare for learning, 2) the implementation aspect is in the good category, the activities include includes applying cognitive and metacognitive strategies, controlling emotions and learning motivation, and carrying out activities, and 3) evaluation aspects are in the good category, the activities include choosing strategies to overcome failure, feeling able to evaluate learning outcomes, reviewing their own work.